ANALYSIS OF VALUE ADDED INTELLECTUAL CAPITAL TO THE FINANCIAL PERFORMANCE OF LISTED BANKING COMPANIES IN INDONESIA - Erliana Banjarnahor (Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2019)
This study aims to find out is there any correlation Value Added Intellectual Coefficient to the financial performance of listed banking company in Indonesia Stock Exchange (IDX). In this research, we using a sample of a banking company that listed during period 2009-2016. We using purposive sampling, there for the number of samples is 23 banks, so for 8 years become total 184. The data analysis technique is using regression multivariate. The result is significant positive impact between Value Added Intellectual Coefficient banking companies’ financial performance, but if the Value Added Intellectual Coefficient components such as value-added capital employed, value-added human capital, structural capital value-added are tested one by one, the outcomes are not significantly impacted on financial performance (return on assets, asset turnover, and assets growth). The limitations of this research are not using market measurement, only using financial measurement.